The Development of Self and Identity in Adolescence: Neural Evidence and Implications for a Value‐Based Choice Perspective on Motivated Behavior - Pfeifer, Jennifer H.; Berkman, Elliot T. (Child development perspectives, 2018)
Following a key developmental task of childhood—building a foundation of self‐knowledge in the form of domain‐specific self‐concepts—adolescents begin to explore their emerging identities in ways that foster autonomy and connectedness. Neuroimaging studies of self‐related processes demonstrate enhanced engagement of the ventromedial prefrontal cortex (PFC) in adolescence, which may facilitate and reflect the development of identity by integrating the value of potential actions and choices. Drawing from neuroeconomic and social‐cognitive accounts, we propose that motivated behavior during adolescence can be modeled by a general value‐based decision‐making process centered around value accumulation in the ventromedial PFC. This approach advances models of adolescent neurodevelopment that focus on reward sensitivity and cognitive control by considering more diverse value inputs, including contributions of developing self‐ and identity‐related processes. It also considers adolescent decision making and behavior from adolescents' point of view rather than adults' perspectives on what adolescents should value or how they should behave.